Copy Adaptation, or How to Translate a Source Product for a Target Market - Cruz García, Laura (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
The aim of this paper is to show the significance of product type and potential buyers’ expectations in ad translation for the production of commercially effective target versions. To this end, this study focuses on adverts for computer products as the referent of the advertising message, and computer users as the addressees. The cultural contexts in contact are the USA and the Spanish markets for these products. The source texts (ST) are adverts from popular USA computing magazines, while the target texts (TT) are from the same type of publications published in Spain. In order to measure the relevance of product type in the translation of these ads, a comparison of the STs and the TTs has been carried out in terms of verbal and non-verbal elements. The strategies used in the translation of these two groups of elements have been described and identified. The results obtained through the analysis of this corpus will shed light on (1) whether the shifts produced in the TTs respond to Spanish computer users’ expectations, that is, whether they are in line with the features of computing ads in Spanish, and (2) whether there are shifts clearly related to the product type.